Clinical trial on tonal tinnitus with tailor-made notched music training. Issue 1 (December 2016) - Stein, Alwina; Wunderlich, Robert; Lau, Pia; Engell, Alva; Wollbrink, Andreas; Shaykevich, Alex; Kuhn, Jörg-Tobias; Holling, Heinz; Rudack, Claudia; Pantev, Christo
Abstract Background Tinnitus is a result of hyper-activity/hyper-synchrony of auditory neurons coding the tinnitus frequency, which has developed due to synchronous mass activity owing to the lack of inhibition. We assume that removal of exactly these frequencies from a complex auditory stimulus will cause the brain to reorganize around tonotopic regions coding the tinnitus frequency through inhibition-induced plasticity. Based on this assumption, a novel treatment for tonal tinnitus - tailor-made notched music training (TMNMT) - has been introduced and was tested in this clinical trial. Methods A randomized controlled trial in parallel group design was performed in a double-blinded manner. We included 100 participants with chronic, tonal tinnitus who listened to tailor-made notched music for two hours a day for three consecutive months. Our primary outcome measures were the Tinnitus Handicap Questionnaire and Visual Analog Scales measuring perceived tinnitus loudness, awareness, distress and handicap. Participants rated their tinnitus before and after the training as well as one month after cessation of the training. Results While no effect was found for the primary outcome measures, tinnitus distress, as measured by the Tinnitus Questionnaire, a secondary outcome measure, developed differently in the two groups. The treatment group showed higher distress scores while the placebo group revealed lower distress scores after the training. However, this effect did not reach significance in post-hoc analysis and disappeared at follow-up measurements. At follow-up, tinnitus loudness in the treatment group was significantly reduced as compared to the control group. Post hoc analysis, accounting for low reliability scores in the Visual Analog Scales, showed a significant reduction of the overall Visual Analog Scale mean score in the treatment group even at the post measurement. Conclusion This is the first study on TMNMT that was planned and conducted following the CONSORT statement standards for clinical trials. The current work is one more step towards a final evaluation of TMNMT. Already after three months the effect of training with tailor-made notched music is observable in the most direct rating of tinnitus perception – the tinnitus loudness, while more global measures of tinnitus distress do not show relevant changes. Trial registration Current Controlled TrialsISRCTN04840953 ; Trial registration date: 17.07.2013